Pendekatan Sosioekonomi Pertanian Berkelanjutan - Sriwidodo Sriwidodo (Jurnal Dinamika Sosial Ekonomi, 2000)
Sustainable agriculture is an alternatif choice to replace the unwise west type agriculture with high chemical input, but the strategy and the technology to be implemented is not ready due to the varied environment. Sustainable agriculture should consider four aspects i.e. ecology/technology, financial/economic, human! institution, and combined. The problem of natural resource and environment in Indonesia is the consequence of several trends, like population growth, deforestation for expanding agricultural land, rapid economic growth in the last three decades, over centralized development planning, and focusing economic development in Java. The dilemma between economic growth and degradation of natural resource base is not always a problem. There should be a new paradigm in the approach of the agricultural development to be long term approach considering to synchronize the conservation of natural resources and the economic development. The new paradigm of the synchronized growth and environment needs to lower the population growth, to maintain the production increase, to lessen the environment impact, to change the human perception, to respect the ecosystems integrity, and to optimize the complementary effects to environment improvement and socioeconomic development. Farming System Development and Farming System Research as holistic approaches are expected can be used to facilitate the production objective and the natural resource conservation objective in agricultural development Simulation model on each agroecological as well as socioeconomic zone can be developed on a farm-household modelKey words: Socioeconomic, sustainable agriculture, conservation of natural resource